Uslub Al-Jinas dalam Surah Al-Insyirah - Widiawati; Mardan; Andi Miswar (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study discusses uslub al-jinās in Surah al-Insyirah with a focus on the beauty of language and the meaning contained in it. Surah al-Insyirah is a Makkiyah surah that has a beautiful style of balaghah language and gives psychological and spiritual influences to readers. This study uses Tafsir al-Munir as the main reference in analyzing the form of al-jinās in the verses of the surah. The results of the study show that there are several forms of al-jināsthat describe the transition from difficulty to ease as the main theme of the surah. The use of words that have similar sounds but different meanings provides a strong language rhythm and emphasizes the message of optimism, fortitude, and peace of mind. In addition, the style of language shows the miracles of the Qur'an in terms of balaghah. This study uses a qualitative method with the approach of ma'nawi and balaghi interpretation. The results of the research are expected to contribute to the development of the study of the Qur'anic balaghah, especially related to uslub al-jinās in the Makkiyah surahs